ANALISIS EFISIENSI PEMASARAN TERNAK KERBAU DALAM KONTEKS BUDAYA KODI DI KECAMATAN KODI BANGEDO - Walla, Yulius Ndara; Pakereng, Yolanda H.I; Neni, Natasya R.N. Lawu; Wala, Anjelita Suartini (BUANA SAINS, 2025)
This study aimed to analyze the marketing efficiency of buffalo livestock in the cultural context of Kodi, Kodi Bangedo District, Southwest Sumba Regency. The research used a mixed-methods approach (quantitative and qualitative) through surveys of 30 farmers, in-depth interviews with traditional leaders and stakeholders, and field observations. The results show that the total marketing value from producers was IDR 1,521,000,000 (98 heads), and the end consumers' purchase value was IDR 1,661,000,000, resulting in a marketing margin of IDR 140,000,000. The average marketing efficiency rate was 27.99%, indicating the marketing system is not yet optimal. Kodi culture plays a significant role in determining distribution patterns and price mechanisms, where transactions are still dominated by social relationships and local networks. This study recommends developing shorter marketing channels and integrating cultural values into marketing strategies to improve farmers' economic efficiency.